Augmented Reality dengan Model Generate Target dalam Visualisasi Objek Digital pada Media Pembelajaran - Randy Permana; Eka Praja Wiyata Mandala; Dewi Eka Putri; Musli Yanto (Universitas Putra Indonesia YPTK Padang, 2023)
Augmented Reality (AR) is a digital technology that allows the creation of a combination between the real world and digital content projections to produce additional valuable information for users. This technology has begun to implement in various fields of human life like industry, health, military, entertainment, and education. AR technology will be applied to the education sector in this community service activity. This activity aims to introduce AR technology and a development model based on the Model Generate Target (MGT) to service partners, namely SMA INS Kayu Tanam. The Generate Target model is an AR application development concept by adopting the concept of Digital Twins, where digital content projections will be made similar to real objects. The projected digital content will serve as a descriptive object from the real world, so users can interact more flexibly with objects from the real world. The activity was carried out by providing an introduction to AR technology, installing AR design software, and practicing making simple AR applications using the MGT concept for partner service to the community. In this activity, the designed AR will use spherical objects in the real world and the resulting digital projection is a virus. Projection of digital content onto spherical objects will provide better information and learning experiences in viral object recognition because 3D objects will appear and be attached to real objects. The expected results of this community service activity are introducing AR technology to partners engaged in education and providing a new solution in implementing new digital content-based teaching media that can be applied to several subjects such as biology, chemistry, and glasses to community service partners.